Keberkesanan Amalan Sistem Penilaian Prestasi: Kajian Kes di Majlis Perbandaran Sungai Petani Kedah (MPSPK) - Rizmi, Riza Citra (2013)
This study was conducted generally to identify the effects of performance appraisal system in Majlis Perbandaran Sungai Petani Kedah (MPSPK). Specifically this study compares the performance appraisal system between J.P.A forms which is often used in MPSPK with Balanced Scorecard (BSC). Data was collected by interview, collecting data in MPSPK and distributing questionnaires. The data then processed using descriptive qualitative and quantitative techniques. Finding from J.P.A showed the performance score decreases for period 2008-2009, however it increases for period 2010. This finding is in line with the number of workers in MPSPK. Finding from BSC shows a more re- presenting result. Financial perspective reflects the increased of the amount of income. Customer perspective reflects the customer satisfaction. Internal business perspective reflects work performance/ which was measured by the number of workers in MPSPK. And for learning and growth perspective reflects income human resource quality and worker’s satisfaction in MPSPK. Overall, BSC findings show a more representative result than the use of J.P.A. Therefore, the use of BSC as an additional performance appraisal system tool will give a better picture for MPSPK.